Cetrolix Protocol versus Conventional Clomiphene Citrate Protocol in Women with Unexplained Infertility Undergoing Intrauterine Insemination: A Randomised Prospective Study - Mostafa F; Farid L (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2016)
Objective: The primary goal of this study was to compare the ovulation and pregnancy rates in women with unexplained infertility undergoing intrauterine insemination utilizing an antagonist (cetrolix) protocol versus the commonly used clomiphene citrate regimen.  Patients and Methods: This was a randomized controlled study performed at Assisted Reproductive Techniques Center of Ain Shams University Maternity Hospital, over a 2-year period, between Jan 2014 and Jan 2016, and included 80 women,with unexplained infertility undergoing intrauterine insemination (IUI), were randomised into two groups. Group I (n=40) received the antagonist protocol: human menopausal gonadotropins were given from Day 2 to reach a dominant follicle of 18-22 mm, intramuscularly. Then, cetrolix (0.25 mg) was subcutaneously started from Day 6 or Day 7 until the day of human chorionic gonadotropins (hCG; that was given in the dose of 10,000 IU, intramuscularly) when follicles reached 18-22 mm. Group II (n=40) receivd the clomiphene citrate protocol: clomiphene citrate given 100 mg/d from Day 2 to Day 6 and then human menopausal gonadotropin (hMG) to reach a dominant follicle of 18-22 mm, intramuscularly. Follow up until day of hCG, afterward, the IUI of 0.5mL was done from 34 hours to 36 hours using IUI catheter without guidance of ultrasonography and with an empty urinary bladder. The primary outcome was clinical pregnancy rate defined as the presence of intrauterine gestational sac detected by ultrasound at 5-weeks' gestation . The number of dominant follicles, level of serum estradiol, and luteinizing hormone at the day of hCG injection and the incidence of twin or triplet pregnancies in both groups were secondary outcome measures.  Results: In this study  Conclusions: It seems that clinical pregnancy rates were significantly higher by cetrolix protocol